2015
DOI: 10.2106/jbjs.o.00148
|View full text |Cite
|
Sign up to set email alerts
|

Defining the “Three-Dimensional Sagittal Plane” in Thoracic Adolescent Idiopathic Scoliosis

Abstract: Routine 2-D measurements of thoracic kyphosis erroneously underestimate the preoperative loss of kyphosis in AIS because of errors associated with axial plane rotation, an inherent component of thoracic scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 20 publications
2
53
0
3
Order By: Relevance
“…These authors also showed that routine 2D measurements of deformities underestimate the amount of Cobb angle because of the axial plane rotation. These techniques have the advantage that a software calculates a 3D reconstruction of the spine based on radiographs of the standing patient [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also showed that routine 2D measurements of deformities underestimate the amount of Cobb angle because of the axial plane rotation. These techniques have the advantage that a software calculates a 3D reconstruction of the spine based on radiographs of the standing patient [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…3-D printing of spine models allows surgeons to more completely understand the anatomy of complex spinal deformities; facilitates better preparation for an operative intervention; and potentially minimizes operative time, blood loss, and the overall risk of neurologic injury. 10,11 We report our experience with additive manufacturing, specifically highlighting 3 complex cases in which our 3-D models were used for preoperative planning and for patient education.…”
Section: Introductionmentioning
confidence: 99%
“…19 This was partially demonstrated by Newton et al,20 who evaluated the angulation between each segment using EOS and observed segmental kyphosis in the curve that is underestimated by the standard radiographic technique. This shows that we have Iittle capacity to produce kyphosis using current posterior techniques, probably because of the conformation of the vertebrae in the structured curves (greater height of the vertebral body in the anterior region and in the convexity in relation to the posterior region and the concavity).…”
Section: Discussionmentioning
confidence: 90%